Aspect Legality and Implementation Criminal To Exploitation Child Sexual Abuse in Indonesia: A Case StudyDecision No. 387/ Pid.Sus /2024/PN Sgl - Barquzzaman, Hartato; Muhammad Adystia Sunggara (KRTHA BHAYANGKARA, 2025)
This research aims to analyze the legal aspects and criminal sanctions related to child sexual exploitation in Indonesia, focusing on the case study of Decision Number 387/Pid.Sus/2024/PN Sgl. Child sexual exploitation is a serious issue that impacts the lives of victims and society. This study examines the application of criminal law as stated in Article 88 in conjunction with Article 76I of Law No. 35/2014 on Child Protection, as well as the challenges in law enforcement in Indonesia. The research utilizes a normative approach with an analysis of related court decisions. The results indicate that although there are clear regulations, challenges remain in the application of criminal law regarding child sexual exploitation, particularly in terms of evidence and victim recovery. The author also recommends the need for stricter law enforcement and more effective strategies to prevent child sexual exploitation in the future.